2021
DOI: 10.1017/gmh.2020.30
|View full text |Cite
|
Sign up to set email alerts
|

An analysis of funding patterns in development assistance for mental health: who, when, what, and where

Abstract: Background Mental health has recently gained increasing attention on global health and development agendas, including calls for an increase in international funding. Few studies have previously characterized official development assistance for mental health (DAMH) in a nuanced and differentiated manner in order to support future funding efforts. Methods Data from the Organisation for Economic Cooperation and Development Creditor Reporting System were obtained through keyword searches. Pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 16 publications
(20 reference statements)
0
2
0
Order By: Relevance
“…The top recipient countries of mental health relevant funding within COVID-19 funding as identified by this analysis are mainly conflict- and disaster-affected (or receiving nations for conflict- and disaster-affected refugees). These results are similar to previous research on international funding for mental health, with DAMH prior to COVID-19 predominantly going towards conflict-affected countries (Gribble et al ., 2021 ). Similarly, previous research has shown the dominance of just a handful of donors in providing mental health funding, including the European Union, Germany, the United States, Norway and Canada, as found in this analysis (Gribble et al ., 2021 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The top recipient countries of mental health relevant funding within COVID-19 funding as identified by this analysis are mainly conflict- and disaster-affected (or receiving nations for conflict- and disaster-affected refugees). These results are similar to previous research on international funding for mental health, with DAMH prior to COVID-19 predominantly going towards conflict-affected countries (Gribble et al ., 2021 ). Similarly, previous research has shown the dominance of just a handful of donors in providing mental health funding, including the European Union, Germany, the United States, Norway and Canada, as found in this analysis (Gribble et al ., 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…These results are similar to previous research on international funding for mental health, with DAMH prior to COVID-19 predominantly going towards conflict-affected countries (Gribble et al ., 2021 ). Similarly, previous research has shown the dominance of just a handful of donors in providing mental health funding, including the European Union, Germany, the United States, Norway and Canada, as found in this analysis (Gribble et al ., 2021 ). This emphasises the narrow range of resources available to support the large burden of mental health globally.…”
Section: Discussionmentioning
confidence: 99%